2000
DOI: 10.1089/15258160050196786
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Stem Cell Mobilization with Cyclophosphamide in Combination with G-CSF, GM-CSF, or Sequential GM-CSF/G-CSF in Non-Hodgkin's Lymphoma Patients: A Randomized Prospective Study

Abstract: We designed a randomized, prospective three-arm mobilization study to determine the kinetics of peripheral blood stem cell (PBSC) mobilization in 60 non-Hodgkin's lymphoma (NHL) patients primed with cyclophosphamide (CTX) in combination with granulocyte colony-stimulating factor (G-CSF) (arm A), granulocyte-macrophage (GM)-CSF (arm B) or GM-CSF/G-CSF (arm C). We also compared mobilization and transplant-related toxicities, pre- and post-transplant support and the probability of survival among the three arms. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…96 Mobilization regimens combining GM-CSF with G-CSF have consisted of sequential or concurrent administration of these agents at a range of doses (G-CSF, 5-10 mg/kg; GM-CSF, 5 mg/kg-250 mg/m 2 ), with or without chemotherapeutic agents. 35,71,97,98 These combination regimens have not been shown to have substantial benefits over regimens that use G-CSF alone; therefore, GM-CSF and G-CSF are not commonly administered together for primary mobilization. However, the combination of G-CSF and GM-CSF is used as a salvage mobilization regimen when mobilization with G-CSF alone has been unsuccessful.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…96 Mobilization regimens combining GM-CSF with G-CSF have consisted of sequential or concurrent administration of these agents at a range of doses (G-CSF, 5-10 mg/kg; GM-CSF, 5 mg/kg-250 mg/m 2 ), with or without chemotherapeutic agents. 35,71,97,98 These combination regimens have not been shown to have substantial benefits over regimens that use G-CSF alone; therefore, GM-CSF and G-CSF are not commonly administered together for primary mobilization. However, the combination of G-CSF and GM-CSF is used as a salvage mobilization regimen when mobilization with G-CSF alone has been unsuccessful.…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…25 In donors with lymphoma, low numbers of circulating natural killer (NK) CD3 À 16 + 56 + cells prior to administration of mobilizing therapies have predicted poor mobilization, 72 as have low platelet counts on the first day of autologous blood stem/progenitor cell collection. 73 Older age was associated with poor autologous mobilization in some patient groups, 30,74,75 but not in others. 74,76 Even though some donors with predictors of poor mobilization respond quite well to mobilizing therapies, 77 poorly mobilizing autologous donors are assumed to have sustained an injury to the hematopoietic stem cell system that is responsible for the poor effect (see Table 4).…”
Section: Autologous Donorsmentioning
confidence: 98%
“…29 In contrast, for patients with non-Hodgkin's lymphoma (NHL), GM-CSF followed by G-CSF permitted more efficient collection of a target number of CD34+ cells than did GM-CSF, while G-CSF was the least efficient of the three cytokine strategies. 30 However, cyclophosphamide plus either G-CSF, GM-CSF or GM-CSF plus interleukin 3 (IL-3) mobilized equally well in another trial. 31 Studies including erythropoietin (EPO) have found that it did 32 and that it did not 33 increase mobilization when added to G-CSF after chemotherapy .…”
Section: Chemotherapy Plus Cytokine(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Several non-randomized or randomized clinical trials have been performed, showing a little or no benefit for sequential administration of standard doses (5-10 mg/kg/d) of GM-CSF and G-CSF. [26][27][28][29][30][31][32][33][34][35][36][37] Neverthelesss, the use of these HGFs was not well explored and particularly the minimal efficient dose for their concomitant administration, following high dose cyclophosphamide (CY). We report here two randomized studies comparing G-CSF to the association of G-CSF and GM-CSF.…”
mentioning
confidence: 99%